Influence of Harvesting and Threshing Methods on Seed Quality of Sunn Hemp (Crotalaria juncea L.) - MASILAMANI,; V ALEX ALBERT,; S VALLAL KANNAN,; M GOVINDARAJ, (Seed Research, 2026)
The present investigation is an attempt to study the effect of different harvesting and threshing methods on germination and seedling vigour of sunn hemp. It was conducted at Agricultural Engineering College and Research Institute, TNAU, Kumulur, Tiruchirappalli, Tamil Nadu during Summer, 2016. The sunn hemp crop was harvested and threshed using four different methods viz., manual harvesting and manual threshing, manual harvesting and mechanical threshing, manual harvesting and tractor treading and harvesting by combine harvester. Studies were also carried out to detect mechanical damage in resultant seeds. Ten days after sowing the harvested seed, the results revealed that the seeds harvested and threshed by manual method maintained 92 per cent germination followed by seeds harvested manually and threshed by tractor treading and combine harvesting (89 per cent). The lowest germination of 83 per cent was recorded by seeds from manual harvest and threshing by mechanical thresher. The physiological parameters of seedling were also on par with germination. From this study, it can be inferred that combine harvester can be recommended for harvesting sunn hemp at 21.5 per cent seed moisture without impairing germination and seedling vigour.